CognIDE: A Psychophysiological Data Integrator Approach for Visual Studio Code - Vieira, Roger Denis; Farias, Kleinner (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Wearable devices capable of capturing psychophysiological data are a reality today. Recent studies indicate that the developer's cognitive indicators (e.g., level of attention and meditation) might affect code comprehension and maintenance tasks. However, current Integrated Development Environments (IDEs) and code editors like Visual Studio (VS) Code fall short of providing contextual information of cognitive indicators located throughout source code. This article proposes CognIDE, a tool-supported approach for integrating psychophysiological data related to cognitive indicators into the VS Code. CognIDE help VS code to push a step forward, providing actionable contextual information alongside the evolving source code. The CognIDE was evaluated through a survey with 6 professionals and interviews for investigating its effects on their perception of usefulness, ease of use, and intention to use in real-world settings. With a high acceptance of the professionals, the emerging results show the potential for using CognIDE to identify and prioritize the review of source code with specific cognitive indicators, mainly related to bugs or inadequate understanding of code snippets.